Effect of aging treatment on the microstructures and mechanical properties evolution of 25Cr-20Ni austenitic stainless steel weldments with different Nb contents. Issue 4 (April 2019) - Zhang, Xu; Li, Dianzhong; Li, Yiyi; Lu, Shanping
Abstract: The microstructure evolutions and the mechanical properties of the 25Cr-20Ni austenitic stainless steel weld metals with different Nb contents were investigated during the long term aging treatment at 700 °C. M23 C6, Nb(C, N), α-Cr phase and Nb-nitride phase (Z phase) were observed in the microstructures of the aged weld metals. The results showed that the α-Cr phase precipitated in the interdendritic regions of the weld metals after being exposed to 700 °C for 500 h and the element Nb accelerated the precipitation of the α-Cr phase significantly. The density of the α-Cr phase decreased with the increase of the distance away from the primary Nb(C, N). Additionally, the α-Cr phase showed a crystallographic relationship with the austenitic matrix, [ 1 1 ¯ 1 ¯ ] α-Cr // [ 1 1 ¯ 0 ] γ and ( 01 1 ¯ ) α-Cr // ( 1 ¯ 1 ¯ 1 ) γ. It was observed that the Z phase precipitated in the periphery of the Nb(C, N) and may replace the Nb(C, N) after long term exposure to high temperature. The transformation of the Nb(C, N) into Z phase suggested that the Z phase had a higher stability than the Nb(C, N) particles at 700 °C for long term aging. The tensile strength of the Nb-bearing weld metal showed a continuous decrease at the initial stage of the aging treatment and then went up slightly with the prolonged aging time. However, the elongations and the impact energies of the weld metals decreased monotonously with the increase of the aging time.